BRIDGING THE DIGITAL DIVIDE IN EDUCATION: A SYSTEMATIC REVIEW (SLR-PRISMA) OF DIGITAL INCLUSION STRATEGIES - Badrud Tamam; Aminudin Aminudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the evolution of research on the digital divide in education and strategies for digital inclusion through a Systematic Literature Review (SLR) of 26 peer-reviewed articles published between 2020 and 2025. Using the PRISMA approach, data were categorized by research focus, year, and journal quality, followed by thematic and bibliometric analysis. The results reveal a significant shift from access-oriented research during the COVID-19 pandemic toward technology-based pedagogical innovation and sustainable digital inclusion strategies. Three main phases emerged: access and digital literacy (2020–2021), pedagogical innovation through Learning Management Systems and Game-Based Learning (2022–2023), and the adoption of Artificial Intelligence and Virtual Reality in inclusive education (2024–2025). Socio-economic and gender factors significantly influence digital literacy outcomes, while technology-driven pedagogy enhances learning participation. The study concludes that effective digital inclusion requires a multidimensional approach integrating social, technological, and policy aspects. The findings provide a theoretical foundation for future research and evidence-based policymaking in equitable digital education.